The Challenges of New Town Development at High-Speed Rail Transit Oriented Development: Case of Jakarta–Bandung HSR - Raden Anggara; Hayati Sari Hasibuan; Chrisna T Permana (Postgraduate, University of Mataram, 2026)
This study examines the development of a sustainable new town based on Transit-Oriented Development (TOD) in Tegalluar to address urban sprawl, inefficient land use, and social inequality. Using a mixed-method approach, data were collected through field surveys, questionnaires, and interviews. Spatial and SWOT analyses were employed to evaluate the characteristics, socio-economic conditions, and community perceptions. The findings reveal Tegalluar's potential as a hub for sustainable activities, supported by adequate transport infrastructure, although public accessibility and supporting facilities remain limited. The SWOT analysis identifies strengths such as strategic location and policy support, weaknesses in public services, opportunities for economic investment, and threats from social inequality. This research recommends strategies to enhance infrastructure, foster community engagement, and integrate public policy with spatial planning to realise sustainable TOD. The model could serve as a reference for new town development in Indonesia to support sustainable urban development.